Validation of online equine-assisted therapy to reduce depression, anxiety, and stress symptoms - Sulaiman, Nursyuhada (2022)
Traditional equine-assisted therapy has provided service face-to-face due to its experiential approach with horses. However, in order to conduct traditional equineassisted therapy it gave implication on high costs of therapy and effect of allergies on patients to animal. Hence, the online therapy has great promises on reduce risk of allergies and costs of delivering mental health care like depression, anxiety and stress. This study aims to design an online equine-assisted therapy and evaluate its effect in reducing depression, anxiety and stress symptoms. This study also underpinned theory of functional equivalence through an imagery technique to deliver the online equineassisted therapy treatment and examined the feasibility of online equine-assisted therapy. Research support the claim that imagery produced same neural action as well as actual physic al approaches and treats the mental health problem. The ADDIE Model was applied in designing the online equine-assisted therapy. In order to evaluate the online equine-assisted therapy in reducing the symptoms, traditional equineassisted therapy and relaxation therapy were compared based on the participant’s DASS-21 score and System Usability Scale (SUS) questionnaire. A sample of fifty participants aged ranging 18 to 54 years old were recruited voluntarily and undergoes all the treatments. The Friedman Test and Wilcoxon Signed Test was selected to analyze the differences within and between groups, respectively. It was found that depression (p = 0.373) and anxiety (p = 0.150) symptoms were no significantly difference among the three treatments. Therefore, compare to the reduction of stress (p = 0.015) symptoms, there are significant different among the three treatments. However, a statistically non-significant result in Wilcoxon Signed Test between online and traditional treatments was found in reducing depression, anxiety and stress. The mean score result for feasibility shows that the online equine-assisted therapy can be accepted and categorized as grade B with good rating. In conclusion, this study shows potential of online equine- assisted therapy in mental health care as it has same effect as traditional equine-assisted therapy. This study suggests to further investigate the effectiveness of online equine therapy in future using the pre and post research method.